Fluctuacion y distribucion de las poblaciones de Oligota minuta Cam. (Coleoptera: Staphilinidae) predator de Mononychellus tanajoa Bondar (Acarina: Tetranychidae) - Guerrero, J.M.; Bellotti, Anthony C.; Reyes, J.A. (International Center for Tropical Agriculture, 1979)
Oligota minuta is one of the major dominant predators of Mononychellus tanajoa, consuming eggs and movil stages of the mite. At the Centro Internacional de Agricultura Tropical, Palmira, Colombia, Oligota adult populations on cassava var. M Col 113 were counted 4 times/day (6 am, 9 am, 1 pm, and 4 pm) to study the distribution of this insect on the plant and the population fluctuation during the day. Oligota populations did not differ significantly during the day, ranging from 10.7-11.3 adults/48 leaves for the different hours sampled. Among the 1st 14 leaves starting at the top of the plant that were sampled the highest Oligota populations were found between the 8th leaf with a range of 16-20 adults/48 leaves. In var. M Col 22 Oligota populations were observed during all 7 mo. of the sampling and its highest densities coincided with the time of highest no. of Mononychellus. (AS)